A thematic analysis of shared experiences of essential health and support personnel in the COVID-19 pandemic. - Linda Carman Copel; Suzanne C Smeltzer; Christine D Byrne; Mu-Hsun Chen; Donna S Havens; Peter Kaufmann; Heather Brom; Jennifer Dean Durning; Linda Maldonado; Patricia K Bradley; Janell Mensinger; Jennifer Yost (PLoS ONE, 2023)
Aims and objectives Studies have shown that the COVID-19 pandemic has taken a toll on individuals who interact with patients with SARS-CoV-2 but focused largely on clinicians in acute care settings. This qualitative descriptive study aimed to understand the experiences and well-being of essential workers across settings during the pandemic. Background Multiple studies of the well-being of individuals who have cared for patients during the pandemic have included interviews of clinicians from acute care settings and revealed high levels of stress. However, other essential workers have not been included in most of those studies, yet they may also experience stress. Methods Individuals who participated in an online study of anxiety, depression, traumatic distress, and insomnia, were invited to provide a free-text comment if they had anything to add. A total of 2,762 essential workers (e.g., nurses, physicians, chaplains, respiratory therapists, emergency medical technicians, housekeeping, and food service staff, etc.) participated in the study with 1,079 (39%) providing text responses. Thematic analysis was used to analyze those responses. Results Four themes with eight sub-themes were: Facing hopelessness, yet looking for hope; Witnessing frequent death; Experiencing disillusionment and disruption within the healthcare system, and Escalating emotional and physical health problems. Conclusions The study revealed major psychological and physical stress among essential workers. Understanding highly stressful experiences during the pandemic is essential to identify strategies that ameliorate stress and prevent its negative consequences. This study adds to the research on the psychological and physical impact of the pandemic on workers, including non-clinical support personnel often overlooked as experiencing major negative effects. Relevance to clinical practice The magnitude of stress among all levels of essential workers suggests the need to develop strategies to prevent or alleviate stress across disciplines and all categories of workers.